Pitch right : the effect of vocal pitch on risk aversion - Chua, Gabriel Yong Ping (2021)
During interpersonal interactions, individual perceptions and judgment are unavoidably influenced by speech cues,such as vocal pitch. This paper experimentally examines the effect of vocal pitch on risk attitudes. In a lottery-choicetask, subjects made a series of binary choices between a 50–50 lottery and a sure outcome option and were asked tolisten to a voice recording verbalizing the payoff information of these options. We manipulated the vocal pitch of thevoice recordings and administered three treatment conditions: control, low-pitch, and high-pitch. We found that ahigher-pitched voice increased risk aversion, while a lower-pitched voice raised risk tolerance. As a relatively smallsample size was employed, the results should be considered preliminary; future replications are indeed necessary toconfirm the robustness and generalizability of the findings.